Pengembangan Aplikasi Computer Based Test dengan Protokol Two Central Facilities - Muhannad Nasyithul Ibad (UIN Sunan Kalijaga Yogyakarta, 2020)
The Indonesian government has issued a policy on Ujian Nasional Berbasis Komputer (UNBK), or it can be called CBT (Computer Based Test). In this study is the development of the CBT system using the Two Central Facilities protocol, which consists of the Central Legitimization Agency (CLA) and the Central Tabulating Facilities (CTF). In developing this CBT system, CLA is used to authenticate the examinees, while CTF is used to provide questions and calculation of exam answers. To maintain security added encryption using the RSA Algorithm (Rivest-Shamir-Adleman) which functions to convert data into ciphertext. From the results of functional trials, this system has succeeded in applying the Two Central Facilities protocol. This system has been connected to the CLA and CTF servers and all data has been successfully encrypted. For this reason, in the future schools will be endeavored to implement the development of the CBT system to avoid fraud.